2008
DOI: 10.1590/s1678-77572008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Surface degradation of composite resins by acidic medicines and ph-cycling

Abstract: This study evaluated the effects of acidic medicines (Dimetapp® and Claritin®), under pH-cycling conditions, on the surface degradation of four composite resins (microhybrid: TPH, Concept, Opallis and Nanofilled: Supreme). Thirty disc-shaped specimens (Ø = 5.0 mm / thickness = 2.0 mm) of each composite were randomly assigned to 3 groups (n = 10): a control and two experimental groups, according to the acidic medicines evaluated. The specimens were finished and polished with aluminum oxide discs, and the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
2
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 27 publications
4
65
2
11
Order By: Relevance
“…Other in vitro studies observed the erosive effects of some medicines, such as antiasthmatic syrups (9), iron supplements (4,6), antiallergic/expectorant medications (5,6,8) and reported enamel surface roughness, microhardness and morphological alteration findings (9). The erosive potential of ferrous sulfate hypothesized by Passos et al (25), was confirmed in the present research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Other in vitro studies observed the erosive effects of some medicines, such as antiasthmatic syrups (9), iron supplements (4,6), antiallergic/expectorant medications (5,6,8) and reported enamel surface roughness, microhardness and morphological alteration findings (9). The erosive potential of ferrous sulfate hypothesized by Passos et al (25), was confirmed in the present research.…”
Section: Discussionsupporting
confidence: 85%
“…Increased acidic food and drink consumption has become the primary extrinsic source of dental erosive agents (1), although acidic medicines and behavioral factors have also been identified as extrinsic etiologic factors in dental erosion (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The longevity of these restorations depends on their abilities to withstand the harsh conditions of the oral environment such as biodegradation [5]. Gopferich et al [6], described the degradation as a "chain scission process during which polymer chains are cleaved to form first oligomers and then monomers".…”
Section: Introductionmentioning
confidence: 99%
“…The palatability of these medicines is increased with the addition of sugars such as sucrose, glucose or fructose to foster patients' acceptability and thus compliance [12,13]. Furthermore, the pH is formulated to optimize their efficacy, and, usually acidic preparations are often necessary for drug dispersion [5,14,15]. Thus, liquid oral medicines may act as extrinsic agents causing biodegradation of resin-based materials, especially if consumed frequently [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation